Descriptions of Problems in Articles Sent to Academic Journals - Ainun Rozana Mohd. Zaid (Journal of Modern Languages)
The aim of this paper is to highlight some of the problems identified by some editors. This paper hopes to help alert, and inform readers and future writers of the possible mistakes that they can ovoid when writing to academic journals. The problems described in this paper are limited to the problems identified and commented in the samples by assessors or referees of the two journals. These problems can also be used as guidelines for future writers who are planning to share their new found knowledge and ideas with their colleagues and interested parties.